Marketing Activities for Developing the Local Potential of Municipalities - Tonkova, Evgeniya (Vallis Aurea, 2015)
Competitiveness of municipalities is a significant factor for their future development. Financing projects that concern the development of local potential for improving their competitiveness attract experts’ attention to effective use of local resources, involvement of population and business, as well as the innovative approaches in managing the municipalities. Highly technological marketing in the public sphere therefore, needs to be viewed as a tool aimed not only at communication and realization of municipal services for population and business, but also as an opportunity for generating ideas, stating consumer interest in coming projects, registering volunteering and implementing donation. Local potential is a dynamic multidimensional category which presupposes disaggregating and further development in various sections. The priorities of municipalities, their comparative advantages, available resources and the support from citizens and businesses are an important landmark in developing local potential. Municipal projects have to be publicly announced in order to receive the support of the population and business. The comparative advantages on the territory of municipalities have to be used actively and developed with the aim at designing a unique identity for better market positioning. Available resources are subject to registering and respective use for achieving favorable direct and transfer socio-economic effect.